2010
DOI: 10.4236/jemaa.2010.21005
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Power Transformer Vibration Features by a Time-Scale-Frequency Analysis Method

Abstract: In order to take advantage of the merits of WPT and HHT in feature extraction from vibration signals of power transformer, a time-scale-frequency analysis method is developed based on the combination of these two techniques. This method consists of two steps. First, the desirable wavelet packet nodes corresponding to characteristic frequency bands of power transformer are selected through a Correlation Degree Threshold Screening (CDTS) technique for reconstructing a time-domain signal that contains useful info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Recent works [17][18][19][20][21][22][23][24][25] exploit vibration measurements for mechanical fault diagnosis of power transformers, but they use a large set of sensors, e.g., at least 10 in [17][18][19], 15 in [22], or 40 in [21] for each transformer. Recent works on power transformer analysis [17][18][19][20][21][22][23][24][25], and battery analysis [45][46][47], adopt computation intensive probabilistic algorithms, not implementable in low-cost embedded computing systems.…”
Section: Critical Analysis Of the State-of-the-art For Ups Predictivementioning
confidence: 99%
See 2 more Smart Citations
“…Recent works [17][18][19][20][21][22][23][24][25] exploit vibration measurements for mechanical fault diagnosis of power transformers, but they use a large set of sensors, e.g., at least 10 in [17][18][19], 15 in [22], or 40 in [21] for each transformer. Recent works on power transformer analysis [17][18][19][20][21][22][23][24][25], and battery analysis [45][46][47], adopt computation intensive probabilistic algorithms, not implementable in low-cost embedded computing systems.…”
Section: Critical Analysis Of the State-of-the-art For Ups Predictivementioning
confidence: 99%
“…Recent works on power transformer analysis [17][18][19][20][21][22][23][24][25], and battery analysis [45][46][47], adopt computation intensive probabilistic algorithms, not implementable in low-cost embedded computing systems. Moreover, the above works usually follow a centralised approach instead of a distributed networking approach as in this paper.…”
Section: Critical Analysis Of the State-of-the-art For Ups Predictivementioning
confidence: 99%
See 1 more Smart Citation
“…7 To further develop the vibration-based condition monitoring method, efforts were also made in the area of signal processing to extract the vibration features of a damaged transformer by advanced signal processing methods, including the wavelet transform, the Hilbert Huang transform, and their combinations. 10 Although the feasibility of using the vibration method for transformer condition monitoring was verified in these case studies, there is still a gap in understanding the physical correlation between the changes in the vibration response and changes in the transformer's mechanical properties associated with the causes of failures. A better understanding of vibration changes caused by transformer mechanical faults is beneficial to fault allocation, even to the development of novel monitoring strategies, which is the research motivation of this work.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that this method provides an option for assessing the mechanical integrity of a transformer. [6][7][8][9][10][11][12] Unlike the DGA and FRA methods, it relies on changes in the vibration response of the transformer under both steady-state and transient processes. For an example, Berler found that looseness in the winding clamping force might cause variations at twice the operating frequency and its harmonics.…”
Section: Introductionmentioning
confidence: 99%